Stereotactic body radiation therapy (SBRT) increases anti-PD-1 antitumor activity by enhancing the tumor immune microenvironment in mice with metastatic hepatocellular carcinoma - Xu, Ke; Gu, Tao; Su, Ke; Liu, Xin; He, Bingsheng; He, Jie; Chi, Hao; Zhou, Xuancheng; Liu, Hanlin; Xiao, Rui; Tang, Xue; Ye, Qinni; et al. (Discover. Oncology, 2025)
Background To explore the effect of radiotherapy on anti-pd-1 anti-tumor activity in metastatic hepatocellular carcinoma. Methods Patients with metastatic HCC treated with intensity-modulated radiation therapy (IMRT) in combination with immunotherapy ( n = 13) were retrospectively analyzed by comparing its efficacy with that of immunotherapy alone ( n = 12) as well as untreated ( n = 20) patients with metastatic hepatocellular carcinoma. Animal experiment used mouse hepatocellular carcinoma H22 cell metastatic tumor model and were also divided into a control group, a PD-1 antibody group, an SBRT group, and an SBRT combined with a PD-1 antibody group. SBRT treatment is 8 Gy×3 F. The growth curves of body weight, irradiated tumor (the primary tumor), and non-irradiated tumor (secondary tumor) were plotted for each group of tumor-bearing mice. For this study, we used flow cytometry to examine effector CD8 + T cells expression in both irradiated and non-irradiated tumors, the CD4 + T and CD4+/CD8 + T cells ratio in the spleen, and used enzyme-linked immunosorbent assays (ELISA) to analyze the concentrations of IFN-γ and IL-10 in serum. Tumors were additionally stained with immunohistochemistry Ki-67 and TdT-mediated dUTP nick end labeling (TUNEL). We used hematoxylin-eosin (HE) staining of liver, spleen, lungs, kidneys, and heart to assess the anti-tumor activity of each group of tumor-bearing mice and their tolerance to determine the safety of the approach. Results Clinical results: The median survival of IMRT + PD-1 group, PD-1 group, and control group were 17.5 months (95Confidence Interval (CI) 13.2–21.8), 12.5 months (95CI 9.0–16.0), and 5.2 months (95CI 5.5–12.9), respectively ( P < 0.001). SBRT combined with PD-1 antibody improved tumor control in both radiated and non-radiated tumors, resulting in a complete cure of the half of mice in animal studies. This was linked to an increased in CD8 + effector T cells infiltration triggered by radiotherapy. HE staining of mice in the SBRT combined with the PD-1 treatment group suggested no damage to the liver, spleen, lungs, kidneys, and heart. Conclusions This study showed that SBRT, while being well-tolerated, significantly increased anti-PD-1 antitumor activity by enhancing the tumor immune microenvironment in mice with metastatic hepatocellular carcinoma without significant toxic side effects. Disclaimer : This manuscript was previously submitted as a preprint only in Experimental Hematology & Oncology and has no conflict of interest with this submission.